Ultrasonographic assessment of thenar muscles for diagnosing sarcopenic obesity in patients with schizophrenia - Yan, Guoyu; Ding, Huaying; Lin, Xia; Li, Zhouyu; Chen, Lanlan; Xiang, Lan; Chen, Xiaoyan; Tan, Youguo (Frontiers in Psychiatry, 2025)
BackgroundPatients with schizophrenia have a high prevalence of sarcopenic obesity (SO) (19.2%), largely due to antipsychotic use and sedentary lifestyle. Conventional diagnostic techniques (e.g., dual-energy X-ray absorptiometry [DXA]) are limited by their cost and complexity.ObjectiveTo evaluate thenar muscle ultrasound (thickness and echo intensity) combined with sex for SO screening and its association with pneumonia and falls.MethodsA total of 490 patients with stable schizophrenia underwent bilateral thenar ultrasonography. SO was diagnosed according to the Asian Working Group for Sarcopenia (AWGS) 2019 criteria (muscle mass, grip strength, gait speed) and the Japanese obesity consensus (body fat ≥20% in males, ≥30% in females, or visceral fat ≥100 cm²). Diagnostic efficacy (ROC analysis) and adverse outcomes were assessed.ResultsPatients with SO (n=94) had significantly reduced thenar muscle thickness (left: 13.81 vs. 14.75 mm, p<0.001; right: 14.83 vs. 15.96 mm, p<0.001) and higher echo intensity (left: 39.57 vs. 35.66, p=0.002; right: 38.52 vs. 34.51, p<0.001) compared with patients without SO (n=396). A model combining right thenar thickness, echo intensity, and gender achieved the best diagnostic performance (AUC = 0.805, sensitivity=73.2%, specificity=76.3%). SO was significantly associated with increased fall risk (adjusted OR = 2.889, p=0.002) and pneumonia (unadjusted OR = 2.175, p=0.038).ConclusionThenar ultrasound combined with sex provides an efficient tool for SO screening (AUC>0.8) in patients with schizophrenia, supporting early intervention to reduce adverse outcomes.